Epitaxial formation of cubic and trigonal Ge-Sb-Te thin films with heterogeneous vacancy structures. (5th February 2017) - Hilmi, Isom; Lotnyk, Andriy; Gerlach, Jürgen W.; Schumacher, Philipp; Rauschenbach, Bernd
Abstract: Preparation of epitaxial Ge-Sb-Te (GST) thin films with heterogeneous vacancy structures is of special interest for data storage applications such as non-volatile random access memory. In this work, epitaxial Ge2 Sb2 Te5 (GST225) thin films grown on Si(111) using pulsed laser deposition technique are reported. Structure analysis utilizing X-ray diffraction and high-resolution aberration-corrected scanning transmission electron microscopy revealed that the as-deposited GST225 films consist of both the cubic (c-GST225) and trigonal (t-GST225) phase. As-grown c-GST225 films exhibit crystalline grains with randomly distributed vacancies (cubic phase I) and with highly-ordered vacancy layers (cubic phase II). The formation of pure epitaxial t-GST225 films with micrometer grain size was achieved by post-annealing of as-grown GST225 films. The GST225 growth is initialized by the formation of a surface passivation Sb/Te layer on the Si(111) substrate surface. The layer is van-der-Waals bonded to the adjacent Te layer of a GST building block. The results of this work shed new insight into the crystal structure of the cubic modifications of the GST225 phase and may promote a better understanding of the switching mechanism of phase change materials as well as they might be beneficial for the future application in multi-level data storage. Graphical abstract: Highlights: Epitaxial growth of Ge2 Sb2 Te5 thin films with three distinct crystalline structures by pulsed laser deposition on Si(111). Co-existence of trigonal and cubic phases (with randomly distributed and highly-ordered vacancies) in a single alloy. Determination of thin film growth mode as the Frank-van der Merwe growth mode. Transformation of as-deposited films into pure trigonal phase with micron-sized grains upon heating for different durations.